Determination of surface properties using speckle metrology: case of special papers - Pino, Abdiel; Pladellorens, Josep (IJRDO-Journal of Applied Science, 2017)
We present an experimental approach to measure of the roughness of the paper on thereal time based in the analysis of speckle pattern on the surface. The image formed byspeckle in the paper surface is considered as a texture, and therefore texture analysismethods are suitable for the characterization of paper surface. The properties statisticalof this speckle pattern are used for estimation and quantification of roughness parameterRa and Rq. We applied digital image processing using statistics of second order,specifically the gray level co-occurrence matrix (GLCM), so this method can beconsidered as non-contact surface profiling method. The results are contrasted toconfocal microscopy, autocorrelation function and fringe projection.